Catalytic Asymmetric Thioacetalization of Aldehydes - Kim, Ji Hye; Tap, Aurélien; Liu, Luping; List, Benjamin (Synlett, 2017)
A catalytic enantioselective thioacetalization reaction has been developed. Various aldehydes react with unsymmetrical 1,3- or 1,2-dithiols to furnish chiral, enantioenriched thioacetals in excellent enantioselectivities upon treatment with a nitrated imidodiphosphoric acid catalyst. The transformation is assumed to proceed via a thionium ion intermediate.
Keywords: thioacetals; imidodiphosphates; Brønsted acid catalysis